2019
DOI: 10.6004/jnccn.2018.7109
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Health Outcomes in Relationship to Hypogonadism After Chemotherapy: A Multicenter Study of Testicular Cancer Survivors

Abstract: Background: This study examined the prevalence of hypogonadism, its clinical and genetic risk factors, and its relationship to adverse health outcomes (AHOs) in North American testicular cancer survivors (TCS) after modern platinum-based chemotherapy. Patients and Methods: Eligible TCS were <55 years of age at diagnosis and treated with first-line platinum-based chemotherapy. Participants underwent physical examinations and completed questionnaires regarding 15 AHOs and health behaviors. Hypogonadism was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 55 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…However, there are still problems to be resolved ( 22 ). Several studies have demonstrated that platinum-based chemotherapy can induce ED ( 10 , 12 , 13 , 23 , 24 ), but ED has not gained the attention of clinicians as a complication. Some scholars have found that oxaliplatin can induce ED in rats by inducing damage to the endothelium of the corpus cavernosum ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still problems to be resolved ( 22 ). Several studies have demonstrated that platinum-based chemotherapy can induce ED ( 10 , 12 , 13 , 23 , 24 ), but ED has not gained the attention of clinicians as a complication. Some scholars have found that oxaliplatin can induce ED in rats by inducing damage to the endothelium of the corpus cavernosum ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…It may also be associated with muscle weakness, depression, osteoporosis, as well as decreased sexual function and fertility 3,75 . Hypogonadism rate of 38.5% has been reported in a study on 491 North American testicular cancer survivors 76 . Hypogonadism in this population could be related to orchiectomy, chemotherapy, radiotherapy, and testicular dysgenesis syndrome (which comprises testicular cancer) 3,77 .…”
Section: Exercise and Hypogonadism In Tgct Patientsmentioning
confidence: 96%
“…3,75 Hypogonadism rate of 38.5% has been reported in a study on 491 North American testicular cancer survivors. 76 Hypogonadism in this population could be related to orchiectomy, chemotherapy, radiotherapy, and testicular dysgenesis syndrome (which comprises testicular cancer). 3,77 Hypogonadism severity is directly linked to the intensity of treatment.…”
Section: Exercise and Late Chemotherapy-related Metabolic Toxicitymentioning
confidence: 99%
“…Late effects after treatment may, to some extent, be caused by lower levels of sex hormones after orchiectomy or oophorectomy as well as being caused by the chemotherapy given. In testicular cancer patients, endocrine hypogonadism is prevalent in 5%-13% of patients after orchiectomy, increasing to 11%-27% after chemotherapy [115,116]. Patients treated for testicular GCT should be followed with regular hormonal assessments according to guidelines, and testosterone replacement therapy is recommended for patients with low testosterone levels and clinical symptoms of hypogonadism [68].…”
Section: Hypogonadism/low Levels Of Sex Hormonesmentioning
confidence: 99%